Structured illumination Mueller matrix imaging - Angelo, Joseph P. (Biomed Opt Express, 2019)
We perform Mueller matrix imaging (MMI) of diffusely scattering phantoms under sinusoidal irradiance of varying spatial frequency. Quantitative polarimetric sensing via MMI completely characterizes a sample’s polarimetric properties, while structured illumination (SI) allows for the control of photon path length. Intralipid phantoms were measured with varying absorption and with varying depth to demonstrate photon path length control for Mueller matrix elements. We observe unpolarized intensity, linear polarization, and circular polarization to depend upon spatial frequency differently. Finally, we measured an ex vivo chicken skin sample over a bright and dark substrate to further demonstrate the sensitivity of SI-MMI to depth.